Using ITS-rDNA and matK gene nucleotide sequences for identification ginseng species in Panax in Phu Xai Lai Leng, Ky Son, Nghe An - Dinh Duy, Vu; Viet Thanh, Tran Thi; Ke Loc, Phan; Minh Tam, Nguyen; Thanh Huong, Nguyen Thi; Hien, Nguyen Thi; Ke Long, Phan (Vietnam Journal of Biotechnology, 2020)
DNA barcoding is a useful tool for species identification using standardized genomic DNA fragments. We used DNA barcodes (ITS-rDNA and matK gene) to explore Panax (32 samples collected from Phu Xai Lai Leng mountain and 19 samples collected from medicinal nursery of TH), and to investigate the phylogenetic taxonomy of Panax. In this study, the PCR success rate for ITS-rDNA and matK region was 100%. The success rate of bidirectional sequencing of PCR product was 100% of ITS-rDNA and matK region with length of 616 bp, 1433 bp, respectively. All 32 samples (Panax TB) of Phu Xai Lai Leng have a close relationship with P. stipuleanatus (MLBS = 99%, BPP = 100%). All 19 samples (Panax TH) of medicinal nursery have a close relationship with P. notoginseng (MLBS = 100%, BPP = 100%). Interspecific genetic distances within and among Panax species was varied from 0.2% to 7.9%, average (4%) (ITS-rDNA gene) and 0.1 to 2.9%, average (1.2%) (matK gene). The genetic relationship of species/gender belonging to the Panax genus showed that they have the same evolutionary origin and discovered that new distributed of P. stipuleanatus in Phu Xai Lai Leng mountain in Vietnam.